2003
DOI: 10.3349/ymj.2003.44.6.961
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Side Effect Profile Due to the Use of Alendronate in the Treatment of Osteoporosis

Abstract: The aim of our study was to evaluate the upper gastrointestinal (GI) tract side effect profile in 759 female patients that had taken alendronate (10 mg/day), for at least 6 months, for the treatment of osteoporosis, in relation to the safety of alendronate and the compliance of patients to its absorption rules. This study was a multicentered retrospective, clinical, non- placebo controlled, study of 759 female subjects carried out at 26 centres in 6 different regions of Turkey. The mean age of our patients was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Although the precise reason of the inhibitory effects of ALD on bone resorption remains to be explored, studies have shown that ALD are internalized by ostoclasts and inhibit bone resorption by indirectly preventing protein prenylation in osteoclasts that cause osteoclast inactivation and apoptosis (24,25). There have also been recent reports on osteonecrosis of the jaws and gastrointestinal side effects as potential complications of bisphosphonate therapy (26)(27)(28), which support the notion that all medications have side effects. Therefore, it is obvious that the risks and benefits of the medication need to be clearly defined.…”
Section: Discussionmentioning
confidence: 83%
“…Although the precise reason of the inhibitory effects of ALD on bone resorption remains to be explored, studies have shown that ALD are internalized by ostoclasts and inhibit bone resorption by indirectly preventing protein prenylation in osteoclasts that cause osteoclast inactivation and apoptosis (24,25). There have also been recent reports on osteonecrosis of the jaws and gastrointestinal side effects as potential complications of bisphosphonate therapy (26)(27)(28), which support the notion that all medications have side effects. Therefore, it is obvious that the risks and benefits of the medication need to be clearly defined.…”
Section: Discussionmentioning
confidence: 83%
“…Fifteen assessed only persistence [17,20,23,33,[36][37][38][39][40][41][42]46,47,52,53] and 12 studies assessed only compliance [18,21,24,[27][28][29][49][50][51][54][55][56]. Eleven studies examined both persistence and compliance [19,22,25,26,34,44,45,48,[57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies contained data from other osteoporosis medications in addition to bisphosphonates [21,26,33,34,[36][37][38][39][40][41][42]48,54,56,58]. Twenty-four studies contained persistence and/or compliance data for OBP therapy only [17][18][19][20][22][23][24][25][27][28][29][43][44][45][46][47][49][50][51][52][53]55,57,59]. Persistence and/or compliance data for daily, weekly or monthly OBPs were compared in 12 studies [17][18][19]23,25,[43][44][45][46][47]52,55].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…I bifosfonati orali, pur essendo utilizzati con successo nella terapia dell'osteoporosi, sono poco assorbiti dal tratto gastrointestinale e la presenza di cibo nello stomaco abbassa ulteriormente la percentuale di assorbimento; anche la tollerabilità gastrointestinale è molto scarsa, infatti per ridurre gli effetti collaterali il farmaco deve essere ingerito con notevoli quantità d'acqua e mantenendo rigorosamente la posizione eretta per almeno mezz'ora: il che li rende totalmente inaccessibili a coloro che sono costretti a letto, anche solo temporaneamente [28].…”
Section: Figuraunclassified